2021
DOI: 10.25073/2588-1094/vnuees.4558
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Stress Distribution in the Song Tranh 2 Hydropower Reservoir: Implication for Induced Earthquake

Abstract: The Song Tranh 2 hydropower reservoir was built in Tra My area, Quang Nam province, composing magmatic and high-grade metamorphic rocks of the northern part of the Kon Tum massif. Since the reservoir was put into operation, induced earthquakes have occurred in the Song Tranh 2 hydropower reservoir and its vicinity. Tectonically, the northwest-southeast to east-west striking faults developed strongly. Detailed analysis of slickensides and attitude of faults occurring in the studied area have shown that the nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies on tectonic stress fields so far have identified that: in the neo-tectonic period, the Song Tranh 2 region has experience the influence of two tectonic phases characterized by the general movement mechanism, the Paleogene–Miocene phase has a sub-latitude direction, and the Pliocene phase up to now has a sub-meridian direction. Under the influence of the shear tectonic stress field by horizontal compression axis of the meridian and sub-meridian, the NW–SE faults have the mechanism of right-lateral strike slip motion, NE–SW faults have the mechanism of left-lateral strike slip motion [ 24 , 25 ]. Earthquakes started occurring in the vicinity of the Song Tranh 2 hydropower since the reservoir was impounded in 2010; before that, no earthquake had been reported in the region.…”
Section: Seismic and Tectonic Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on tectonic stress fields so far have identified that: in the neo-tectonic period, the Song Tranh 2 region has experience the influence of two tectonic phases characterized by the general movement mechanism, the Paleogene–Miocene phase has a sub-latitude direction, and the Pliocene phase up to now has a sub-meridian direction. Under the influence of the shear tectonic stress field by horizontal compression axis of the meridian and sub-meridian, the NW–SE faults have the mechanism of right-lateral strike slip motion, NE–SW faults have the mechanism of left-lateral strike slip motion [ 24 , 25 ]. Earthquakes started occurring in the vicinity of the Song Tranh 2 hydropower since the reservoir was impounded in 2010; before that, no earthquake had been reported in the region.…”
Section: Seismic and Tectonic Settingsmentioning
confidence: 99%
“… Spatial distribution of earthquake epicentres during the period of September 2012 to March 2020 (dark circles) and faults on the background of geology given by Hoai et al [ 25 ]. The seismic stations are indicated by building symbols.…”
Section: Figurementioning
confidence: 99%